The Power of Language: How English Literature Influences Society - Bakbergenov Aybek (Journal of Learning on History and Social Sciences, 2024)
This article explores the power of English literature to influence society by examining its role in reflecting social issues, fostering empathy, challenging norms, and driving social change. It highlights the impact of English literature on cultural identity, education, and societal progress, emphasizing its ability to provoke thought, inspire creativity, and shape a more inclusive and enlightened society.